PTU-192 Management of anal intraepithelial neoplasia (AIN): a multicentre audit. (22nd June 2015) - Lin, DJ; Ali, M; O'Connell, D; Harmston, C
Abstract : Introduction: Anal intraepithelial neoplasia (AIN) although rare is a precursor to anal squamous cell cancer (SCC). There is little evidence on the effectiveness of follow-up protocols. This audit aimed to assess the compliance with follow-up guidelines from The Association of Coloproctology of Great Britain and Ireland (ACPGBI). Method: A retrospective multicentre audit was performed, all patients with histologically confirmed AIN from 1 Jan 2008 were identified from the cancer network pathology database with a centralised anal MDT. Assessment, follow-up, and outcomes were obtained from the hospitals clinical results reporting system and compared to the ACPGBI published guidelines on AIN. Results: There were a total of 24 patients, 37.5% male (n = 9), with AIN. Mean age 58 (range 20–94). Mean follow-up time 24 months (range 2–65). 16.6% had AIN1 (n = 4), 16.6% had AIN2 (n = 4), 66.6% had AIN3 (n = 16). Of the patients diagnosed with AIN3, 75% (n = 14) were discussed at anal MDT, 100% (n = 16) had guideline compliant follow-up. Of the 8 patients with AIN1 or AIN2, 62.5% (n = 5) had at least 6 monthly follow-up, 43.7% (n = 7) of patients with AIN3 had a re-biopsy of the site of lesion. 1 (6.5%) patient with AIN3 progressed within 1 year to squamous cell carcinoma. 75% of female patients with AIN were managed with a gynaecologist. Conclusion: This study showed that, once diagnosed with AIN, there is good compliance with guideline focused follow-up, and the majority of patients are discussed in a centralised anal MDT. Progression to anal cancer was in keeping with that seen in other studies. Disclosure of interest: None Declared.